Hubungan Sanitasi Lingkungan dengan Stunting pada Anak Balita di Daerah Pesisir Pantai Puskesmas Tumalehu Tahun 2020 - Inamah Inamah; Rahwan Ahmad; Wahyuni Sammeng; Hairudin Rasako (Poltekkes Kemenkes Maluku, 2021)
Poor environmental sanitation will result in diarrheal disease which will later lead to infection and thus lead to malnutrition. In Indonesia, it is recorded that 7.8 million out of 23 million children under five are stunted or around 35.6%. Based on the Tumalehu Health Center report (November 2019), it shows that in 2019 the number of children under five was 1467 and those with poor nutritional status were 89 children (6.07%). The research objective was to analyze the relationship between environmental sanitation and stunting in children under five in the coastal area of Tumalehu Health Center. This research method is analytic observational with a cross-sectional approach, the number of samples is 313 toddlers. Data were analyzed using Chi Square Test. The results of the study using a bivariate test showed that there was a relationship between environmental sanitation, consisting of clean water facilities (p=0.014), SPAL (p=0.05) and waste disposal facilities (p=0.00) with the incidence of stunting (HAZ) in toddler. The conclusion from the research is that poor sanitation can contribute to nutritional problems, in this case a picture of past nutrition problems for children under five, which is indicated by stunting.